Women's Reproductive Health Rights in the Tradition of Consanguineous Marriage at the Madura Islamic Boarding School - Rifki Rufaida; Mohammad Thoyyib Madani (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2025)
Women's reproductive health rights mean the authority of a woman to obtain a healthy condition, whether physically healthy, psychologically healthy and socially healthy, which is related to her reproductive system and reproductive processes. Women's reproductive health rights have been regulated in many Indonesian laws, namely the 1945 Constitution, Article 28H, Law No. 39 of 1999 concerning Human Rights (HAM), Law No. 23 of 2002 concerning Child Protection, Law No. 17 of 2023 in conjunction with Law No. 36 of 2009 concerning Health, and Article 5 of Law Number 23 of 2004 concerning the Elimination of Domestic Violence. (PKDRT). Taking a closer look at women's reproductive health rights, especially in the tradition of consanguineous marriages that occur in Madura Islamic Boarding Schools, the law is considered to provide little guarantee regarding women's reproductive health rights. Therefore, this incident requires legal protection to safeguard and/or maintain society in order to achieve justice, because in essence the aim of the law is to achieve justice. Fulfilling justice for women in reproductive health rights is a form of realizing women's human rights (HAM). The research method used is empirical legal research; obtained from interviews and real behavior carried out through direct observation. Meanwhile, the approach used in this research is a descriptive qualitative approach. The results of the research found, firstly, that there is neglect of women's reproductive health rights in the consanguineous marriage tradition in Madura Islamic boarding schools, such as the right to choose a partner, secondly, the right to enjoy sexual relations, thirdly the right to determine pregnancy, fourthly the right to care for and care for children, and fifthly, limited access to information about women's reproductive health rights.